Electrospun polyethersulfone/Ag-Clinoptilolite to remove chemical oxygen demand from real wastewater. Issue 9 (November 2021) - Zendehdel, Mojgan; Nouri, Faezeh Hossein
Ag-Clinoptilolite/Polyethersulfone (PES/Clin/AgNPs) nanofiber was synthesized through the electrospinning method. The effect of solvent, the amount of Ag-Clinoptilolite, and PES were investigated. Parameters such as electric field, spinning distance, and concentration of the dope solution were studied in order to demonstrate their effects on the electrospinning ability and morphology of the nanofiber. The structure of PES/Clin/AgNPs nanofiber was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX) analyses. In the optimum conditions, the nanofibers could be prepared at the size of 250–800 nm. Then, their ability to remove chemical oxygen demand (COD) from real wastewater was studied. The result revealed about 85% removal of COD at pH = 10 and in 10 min for PES/Clin/AgNPs (25%). A successful fabrication method using low-cost natural zeolite and the green polymer was introduced. The reusability of the column was assessed.